Penentuan Umur Simpan Jajan Pia Nangka Menggunakan Metode ASLT (Accelerated Shelf Life Testing) Berdasarkan Model Kandungan Air Kritis - Adiasih, Ni Made Juli; Gunadnya, I. B. Putu; Yulianti, Ni Luh (Jurnal BETA (Biosistem dan Teknik Pertanian), 2017)
The objectives of this research were to determine the shelf life of jackfruit pia use ASLT method (Accelerated Shelf Life Testing) based on critical moisture content model. Jackfruit pia was packed in two types of packaging, namely cellophane and LDPE packaging which were stored in three different storage humidity, such as 89,7%, 92,2% and 96,7%. Observation on each parameter was done every 2 days. Parameters were measured by organoleptic tests in some catagories such as visual parameters, color, aroma, texture, and flavor. Supporting parameters to determine the shelf life of jackfruit pia were initial moisture content (Ma) 0.12 g, critical moisture content (Mc) 0,15 g, packaging permeability (k/x) of cellophane 0,15gH2O/m2.day.mmHg and LDPE 0.09 gH2O/m2.day.mmHg, packaging area (A) of cellophane 0,015 m2 and LDPE was 0,021 m2, the weight of the samples per pack was (Ws) 25,71 g and ?P was 2,66 mmHg. The calculation of ASLT method showed that the shelf life of jackfruit pia which stored at RH 75% which was packed with cellophane packaging was 129 days (4,3 months), in addition shelf life pia with LDPE packaging was 153 days (5,1 months).
Keywords: Shelf life, jackfruit pia, ASLT method, critical moisture content, cellophane, LDPE